Delay Bounded Roadside Unit Placement in Vehicular Ad Hoc Networks - Peng Li; Chuanhe Huang; Qin Liu (International Journal of Distributed Sensor Networks)
The placement of roadside units (RSUs) is a difficult and yet important issue in vehicular networks. If too few RSUs are placed, the system performance would be very poor. However, with too many RSUs, it would incur high installation cost and maintenance cost of these RSUs. In this paper, we study the problem of delay bounded roadside unit placement (DRP) in vehicular networks. For a given delay bound, our objective is to place the minimal number of RSUs in the system such that a message from any of RSUs in the region can be disseminated to all vehicles within the given delay bound. We consider two cases of RSUs, the case that all RSUs are interconnected through wired lines (called DRP-L problem) and the case that RSUs connect to other RSUs through wireless link (called DRP-W problem). We first prove that both DRP-L and DRP-W problems are NP-hard. Then, we propose several heuristic algorithms to solve DRP-L and DRP-W problems, respectively. Extensive simulations have been conducted to show that the performance of our proposed methods is superior to the other methods.